THE ADJUDICATION PROCESS OF INTERNATIONAL COURT OF JUSTICE ON PEDRA BRANCA/PULAU BATU PUTEH DISPUTE BETWEEN MALAYSIA AND SINGAPORE - Gesta Fauzia Nurbiansyah (2013)

(untitled)
After several decades the nation-state was unable in settle of several issues and problems between states through diplomatic negotiation. The International Organization began to appear, changed the nation-state as a primarily actor in political affairs. The International Court of Justice (ICJ) a principal organ of the United Nations (UN) as the biggest International Organization has believed as the best adjudication way in disputes settlement between states, such as territorial dispute. Hence, i